2013
DOI: 10.1149/2.064401jes
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cathode Fabrication on Fuel Cell Performance

Abstract: Hydrophobicity is generally believed to be key to water management in polymer electrolyte fuel cells (PEFCs). However, we reported that the membrane electrode assembly (MEA) using a hydrophilic micro porous layer (MPL) showed much better performance in a wide range of pressure and humidity conditions than that using a hydrophobic MPL. When operating an MEA, it usually needs to be humidified in order to maintain conductivity of the membrane. Operation without humidification is critical to the commercialization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…This result is consistent with the results by Tanuma et al which were obtained by using a single cell with an active area of 25 cm 2 in wet conditions (80 • C, 100%RH). 20 The limiting current densities of the cell using the GDE method are higher than those using the decal transfer method. The differences in the cell voltages of the two types of MEA increase as the cell temperature decreases.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the results by Tanuma et al which were obtained by using a single cell with an active area of 25 cm 2 in wet conditions (80 • C, 100%RH). 20 The limiting current densities of the cell using the GDE method are higher than those using the decal transfer method. The differences in the cell voltages of the two types of MEA increase as the cell temperature decreases.…”
Section: Resultsmentioning
confidence: 92%
“…20 The authors also investigated the effect of the MPL/CL interface, and the results showed that an MEA made by the GDE method increases the cell voltage under wet conditions over those of an MEA made with the decal method at specific temperature conditions. 19 These results suggested that a smooth MPL/CL interface without gaps could be expected to prevent water accumulation and so improve cell performance.…”
Section: F360mentioning
confidence: 99%
“…This section investigates the effect of the interfacial structure at the contact between the CL and the MPL on the cell performance using two types of membrane electrode assemblies (MEAs) on the cathode side. These MEAs were experimentally produced by Asahi Glass Co., Ltd. [18,19]: one was manufactured by a conventional decal transfer method which combines -10 -a hydrophobic MPL coated GDL and a CL by hot-pressing, and the other was made by a gas diffusion electrode (GDE) method which directly coats a hydrophobic MPL surface with catalyst ink to form a CL at the cathode side (the decal transfer method was applied at the anode side) [18,19]. Because of the direct coating of the MPL with the CL, it may be assumed that there is an interfacial structure without large gaps between the CL and the MPL with the GDE.…”
Section: Effect Of Interfacial Structure At the CL And Mpl Contactmentioning
confidence: 99%
“…20 As a reference GDL for the anode, a commercially available GDL (X0086 IX92 CX320, hydrophobically treated GDL with an MPL, Freudenberg-NOK) was used.…”
Section: Methodsmentioning
confidence: 99%
“…16 Departing from the conventional design of MPLs using PTFE, we conceived the idea of hydrophilic MPLs consisting of carbon fiber and ionomer, and reported that the MEA employing a hydrophilic MPL on the cathode side exhibited much better performance in a wide range of pressure and humidity than that using a hydrophobic MPL. [17][18][19][20] The hydrophilic MPL consists of ionomer and vapor-grown carbon fiber with a fiber diameter of 150 nm, and in addition to that, thorough consideration to the surface nature (hydrophobicity/hydrophilicity) of the MPL was given in our previous paper. 18 We applied our technique of preparing a carbon fiber dispersion to the fabrication of MPLs using carbon particles and carbon fibers with various fiber diameters.…”
mentioning
confidence: 99%